Narrative of the life of Frederick Douglass, an American slave, written by himself : With related documents - Douglass, Frederick; Blight, David W. (Boston Bedford/St. Martin's, 2003)
This second edition of Douglass's Narrative reprints this classic document together with speeches and letters, all in a volume designed for undergraduate students. An extensive introduction places the Narrative in its historical and literary contexts with annotations on needed background.
Includes bibliographical references (p. 181-182) and index
Keywords: Tham khảo